М.ЮСУФ ШЫҒАРМАЛАРЫНДА ТАЛМЕҲ УСЫЛЫНЫҢ ҚОЛЛАНЫЛЫЎЫ - Прекеева, А.; Қутлымуратов, К. (SCIENCE and SOCIETY, 2022)
The article is devoted to the art of talme in the work of M. Yusuf. The names of famous historical figures, examples from the names of epics and legends are given and interpreted.
Keywords: Talmekh art; history; historical figures; historical works; epic poem; legend; names of ancient positions; names of lands and waters